CULTURAL FACTORS IN THE ETIOLOGY OF MENTAL DISORDER AND THEIR IMPACTS ON CLINICAL SYMTOMS AND INTERVENTION - Djamaludin Ancok (Faculty of Psychology Universitas Gadjah Mada, 1996)
The study on impacts of culture on mental disorder has drawn attention of researcher in the field of psychology and psychiatry. Culture has been defined in different ways by different researcher. A number of researcher has defined culture in terms of differences in ethic groups (e.g. Gossop, 1994).